Flow injection analysis : instrumentation and applications - Trojanowicz, Marek (World Scientific, 2000)
The concept of flow injection analysis (FIA) was introduced in the mid-seventies. It was preceded by the success of segmented flow analysis, mainly in clinical and environmental analysis. This advance, as well as the development of continuous monitors for process control and environmental monitors, ensured the success of the FIA methodology. As an exceptionally effective means of mechanization for various procedures of wet chemical analysis, the FIA methodology, in use with a whole arsenal of detection methods of modern analytical chemistry, proved to be of great interest to many. The fast and intensive development of the FIA methodology was due to several factors essential for routine analytical determinations, such as very limited sample consumption, the short analysis time based on a transient signal measurement in a flow-through detector and an on-line carrying out difficult operations of separation, preconcentration or physicochemical conversion of analytes into detectable species. Twenty-year studies by numerous research groups all over the world have provided significant progress in the theoretical description of dispersion phenomena in FIA and various operations of physicochemical treatment of the analyte. This volume is devoted to the presentation of the current status of development of the instrumentation for FIA and the many fields of its practical applications, based on an extensive bibliography of original research publications.
Keywords: biologie